Technical and economic design of a novel hybrid system photovoltaic/wind/hydrokinetic to supply a group of sustainable buildings in the shape of airplanes. Issue 3 (March 2023) - Icaza, Daniel; Borge-Diez, David
Abstract: This research analyzes the impact of a hybrid off-grid renewable energy system consisting of wind turbines, solar photovoltaic, hydrokinetic turbines and battery-backed to provide a group of novel airplane-shaped buildings, generates development in nearby towns that sit on a city vantage point from Cuenca in Ecuador. This is an innovative proposal that, in addition to using renewable energy in the complex of buildings, generates development in nearby towns. Three sources of renewable energy under energy control, load cycle and load monitoring are used to determine new patterns in the behavior of the sources with respect to the demand for electricity. Above all, it reduces carbon. With the support of HOMER Pro, the generation sources are optimized to cover the electrical demand patterns of the group of buildings in the form of airplanes. The results show that the systems that include solar panels, wind and hydrokinetic generators have a higher cost but there is more guarantee by maintaining their charge levels in the batteries above 40%. The proposed methodology and design can be widely adapted to places with similar characteristics worldwide, creating a novel solution for this type of buildings powered by renewable energy. The annual energy required by the set of buildings is 234.86 MW h/year. When projecting the renewable energy system for 25 years, an NPC of 37, 600 and a COE of 0.386/kWh are achieved.